Analysis of Student Learning Difficulties at MA AL-Kautsar Pekanbaru in Physics Subjects in the Kinematics of Rectilinear Motion Material - Fauza, Naila; Aden, Aden; Islami, Nur (Journal of Educational Sciences, 2025)
This research aims to identify the level of learning difficulties faced by students in physics at a private school in Pekanbaru. The research subjects consist of students from class IX MIPA of the science department. The method used is a descriptive qualitative approach, where data is collected through questionnaires distributed to the students. The research results show that the learning difficulties experienced by the students are influenced by internal factors, such as students' intelligence and motivation. These factors lead students to perceive physics learning as difficult, and they struggle to understand the material presented by the teacher and apply it to problems. Therefore, strategies are needed to improve students' understanding of physics learning at MA AL Kautsar Pekanbaru.